Marilia caramuru sp. nov. and Marilia paraguassu sp. nov. (Trichoptera: Odontoceridae), two new species from Maranhão State, Northeast Brazil - Rocha, Isabela C.; Souza, Wagner Rafael M. (Zootaxa, 2018)
Although the world species diversity of Marilia Müller 1880 is not great, knowledge about this group may be underestimated, since several areas are poorly studied, especially in Northeast Region, Brazil. Two new species are described and illustrated here based on specimens collected in Maranhão State, from which the genus has not been reported previously. Despite the similarity of Marilia caramuru sp. nov. with M. elongata Martynov 1912, differences between them are observed especially in segment X and preanal appendages, in addition to details of wing venation. The unique set of spiniform projections on endotheca, and the wrinkled prominence on sternum VIII distinguish Marilia paraguassu sp. nov. from all other species in the genus. The material examined has been deposited in the Coleção Entomológica Professor José Alfredo Pinheiro Dutra, UFRJ, Rio de Janeiro, Brazil, and in the Coleção Zoológica do Maranhão, UEMA, Maranhão, Brazil.